Is There a Penalty for Becoming a Woman? Is There a Premium for Becoming a Man? Evidence from a Sample of Transsexual Workers - Lydia Geijtenbeek; Erik Plug (Institute for the Study of Labor (IZA), 2015)
We study the earnings of transsexuals using Dutch administrative labor force data. First, we compare transsexuals to other women and men, and find that transsexuals earn more than women and less than men. Second, we compare transsexuals before and after transition using worker fixed effects models, and find a fall in earnings for men who become women and a smaller rise (if any) in earnings for women who become men. These earnings patterns, which hold for annual as well as hourly earnings, are consistent with a labor market model in which workers are discriminated for being female and transsexual.
Keywords: J16; J24; J71; 330; transsexuals; gender; labor market outcomes; discrimination